110k views
5 votes
Express as a trinomial.
(3x+5)(2x+9)

2 Answers

3 votes

Answer:


6x^(2) +37x+45

Explanation:

Hello!

A trinomial is a algebraic expression containing 3 terms

To turn this into a trinomial we have to multiply everything by each other

3x

3x * 2x = 6x^2

3x * 9 = 27x

5

5 * 2x = 10x

5 * 9 = 45

Now we put it all together

6x^2 + 27x + 10x + 45

Combine like terms

6x^2 + 37x + 45

The answer is
6x^(2) +37x+45

Hope this helps!

User KalC
by
6.7k points
1 vote
The answer is 6x2+37x+45
User Hendraspt
by
6.2k points